Managing yourself - Walmsley, Bernice (London : Hodder education, 2010)
Part of a vital series for today's manager, produced in conjunction with the Chartered Management Institute, 'Instant Manager: Managing Yourself' is for managers who want to take their career all the way. Practical and down to earth, it concludes with a fascinating interview with Andy Green, CEO of Logica
1. Introduction -- 2. What personal recources do you need to do your job --3. How would setting objectives improve your performance? -- 4. How can you fill any GAPS in your current skills? -- 5. What do you need to do to develop yourself professionally? -- 6. How can you make the best use of you time? -- 7. How does you work role fit into your organisation? -- 8. How can you obtain, and then use, useful feedback? -- 9. What are your personal values and how do they affect your career? -- 10. Can networking help you in your work role? -- 11. How can you develop your personal networks? -- 12. The companion interview: andy green on managing yourself
Includes bibliographical references (p. [245]-247) and index
Keywords: Career development; Executives; Management; Self-management (Psychology)